Taxes and Risk Sharing. - Fellingham, John C.; Wolfson, Mark A. (The Accounting Review, 1985)
ABSTRACT: Models that characterize Pareto-efficient sharing of joint venture profits or constrained Pareto-efficient sharing of income in principal-agent contracting problems have ignored tax considerations. We extend the theory by showing that the effect of taxes on optimal contracting (both in the face of and in the absence of moral hazard problems) is related to the effect of changes in risk attitudes towards lotteries over pre-tax income. For example, optimal contracts will reflect the tax-induced demand for insurance of a risk-neutral individual who faces a progressive income tax schedule; that is, the risk-neutral individual will not bear all the risk, and in the face of moral hazard on the act selection of a risk-neutral agent, demand for monitoring will be created where none existed in the absence of the progressive tax. We also show that Pareto-optimal risk-sharing contracts do not generally result in expected tax minimization, even when taxes are modeled as a deadweight loss to the system.